Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Synthesis, characterization and single crystal x-ray structures of trifluroacetylacetonate copper(ii) complexes - Kumari, Neha; Bahadur, Vir; Butcher, Raymond J.; Kumbhar, Anupa A. (Journal of Chemical Crystallography, 2022)
{Three Cu(II) complexes of 1,1,1-trifluoroacetylacetonate, viz. [Cu(TFACAC)(2)(MeOH)] (1), [Cu(TFACAC)(2)(py)] (2) and [Cu(TFACAC)(2)(DABCO)] (3) were synthesized and characterized by elemental analysis, IR, UV-Visible spectroscopy and cyclic voltammetry. Structures of complexes 1-3 were established by single crystal X-ray diffraction wherein 1 and 2 adapt square pyramidal geometry. Complex 1 crystallizes in triclinic space group P-(1), with a = 8.5059(6) angstrom
Keywords: Copper(II) complexes; crystal structure; cyclic voltammetry; DABCO; Pyridine; Trifluoroacetylacetone